Sequence and structure-based comparative analysis to assess, identify and improve the thermostability of penicillin G acylases. (1st November 2015) - Panigrahi, Priyabrata; Chand, Deepak; Mukherji, Ruchira; Ramasamy, Sureshkumar; Suresh, C G
Abstract: Penicillin acylases are enzymes employed by the pharmaceutical industry for the manufacture of semi-synthetic penicillins. There is a continuous demand for thermostable and alkalophilic enzymes in such applications. We have carried out a computational analysis of known penicillin G acylases (PGAs) in terms of their thermostable nature using various protein-stabilizing factors. While the presence of disulfide bridges was considered initially to screen putative thermostable PGAs from the database, various other factors such as high arginine to lysine ratio, less content of thermolabile amino acids, presence of proline in β-turns, more number of ion-pair and other non-bonded interactions were also considered for comparison. A modified consensus approach designed could further identify stabilizing residue positions by site-specific comparison between mesostable and thermostable PGAs. A most likely thermostable enzyme identified from the analysis was PGA from Paracoccus denitrificans ( Pd PGA). This was cloned, expressed and tested for its thermostable nature using biochemical and biophysical experiments. The consensus site-specific sequence-based approach predicted Pd PGA to be more thermostable than Escherichia coli PGA, but not as thermostable as the PGA from Achromobacter xylosoxidans . Experimental data showed that Pd PGA was comparatively less thermostable than Achromobacter xylosoxidans PGA, although thermostability factors favored a much higher stability. Despite being mesostable, Pd PGA being active and stable at alkaline pH is an advantage. Finally, several residue positions could be identified in Pd PGA, which upon mutation selectively could improve the thermostability of the enzyme.